2006
DOI: 10.1038/sj.onc.1209978
|View full text |Cite
|
Sign up to set email alerts
|

Normal cellular senescence and cancer susceptibility in mice genetically deficient in Ras-induced senescence-1 (Ris1)

Abstract: Oncogenic Ras triggers a permanent cell-cycle arrest known as oncogene-induced senescence (OIS) that constitutes a relevant tumor suppressor mechanism. Ris1 (Ras-induced senescence-1) is a novel gene that was identified in a screen as specifically upregulated during Ras-induced senescence, and that is located at a chromosomal region, 3p21.3, frequently lost in human cancer. Moreover, Ris1 is highly conserved in vertebrates, does not present paralogs, and its sequence does not reveal similarities with other pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Our results were consistent with the previous study that found that TMEM158 was an upregulated gene in Ras-senescent human fibroblasts and expected to negatively regulate cell cycle [ 8 ]. However, another study indicated that TMEM158-deficient mouse embryonic fibroblasts showed no apparent change in cellular functions, such as proliferation, senescence and oncogenic transformation [ 19 ]. The discrepancy may due to differences in cell types and experimental models.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were consistent with the previous study that found that TMEM158 was an upregulated gene in Ras-senescent human fibroblasts and expected to negatively regulate cell cycle [ 8 ]. However, another study indicated that TMEM158-deficient mouse embryonic fibroblasts showed no apparent change in cellular functions, such as proliferation, senescence and oncogenic transformation [ 19 ]. The discrepancy may due to differences in cell types and experimental models.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have implicated a role for Rasl11b subgroup members in oncogenesis. For instance, rasl11a mRNA is less abundant in some prostate cancers [38] , ris / rasl12 tumor suppressor function in breast cancer is controversial [37] , [62] , and rerg expression inhibits tumor formation in nude mice and is decreased or lost in primary human breast tumors [39] . Thus, clarifying the biological role of this subgroup of small GTPase necessitates further studies.…”
Section: Discussionmentioning
confidence: 99%
“…RIS1 has recently been identified as a target in the mutator pathway of colorectal cancers exhibiting microsatellite instability, where mutations have been observed in the CGN codon repeat tract that encodes 14 alanines 68. In order to deduce the molecular function of the gene, a homozygous RIS1 ‐null mouse knockout was created recently 69. Although there were no overt changes in embryonic development, adult physiology, or frequency of tumor formation, following chemical induction, further studies are warranted as a modest (although not statistically significant) increase in tumor size was observed in the RIS1 ‐null mice.…”
Section: Discussionmentioning
confidence: 99%